Buryat-Mongol and Alash autonomous movements before the Soviets, 1905-1917 - Sablin, Ivan; Korobeynikov, Alexander (AlterNative, 2016)
Despite the Stalinist myth, it was not the Bolsheviks but Indigenous intellectuals who introduced autonomy as a form of post-colonial settlement during the crisis and collapse of the Russian Empire to Siberia and Central Asia. Employing a comparative perspective, this article traces the development and implementation of two autonomous projects in Asian Russia. The Buryat-Mongol and Kazakh (Alash) Indigenous intellectuals synthesized local ideas and the globally circulating notions of national self-determination, enlightenment and democracy when articulating political unity of Indigenous peoples in national terms. By advocating their broader representation in existing and envisioned power structures they fought against discrimination and protected native languages and other forms of cultural expression from assimilation. This article shows that these Indigenous intellectuals were not silent recipients of the policies coming from the imperial and post-imperial centers but actively engaged in designing and ensuring the future of their communities.
Gesehen am 27.05.2017